Characteristics of the starting material of stockolus bezos for lawn use - Marinich, L.; Shakaliі S.; Bahan, A. (Scientific Progress & Innovations, 2022)
A small number of species of perennial grasses are used to create lawns in Ukraine. Among the large species composition (the group of fodder grasses includes more than 600 species of plants), the greatest fodder value is the thornless cornflower, which is used for green fodder, silage, hay and grass flour. But increasingly, plants of this culture are used in garden compositions, planted in gardens, front gardens, along the edge of lawns, in flower gardens. Tall specimens can play the role of a hedge in the country. This is facilitated by a number of advantages: drought resistance, frost resistance, undemanding to growing conditions. The purpose of the research was to evaluate the samples of the seedless cornflower in order to identify the forms that belong to low-growing (ground) cereals and to select the breeding material based on a set of productivity and resistance to adverse environmental factors in combination with decorativeness. In the process of research, field and quantitative methods, the test beam method, weight, and statistical methods were used. According to the results of the study of the root forms of the thornless cornflower in the collection nursery, it is possible to recommend Aeneas, Universe, D07, K35591 as the starting material for creating lawn-type varieties. Samples of Aeneas have good winter hardiness, quickly restore vegetation in the spring, do not form clumps, have a rich dark green color of the leaf plate, high winter hardiness, resistance to shedding and falling out, and good decorativeness. The Universe sample has a high score of decorativeness, green color of the leaves, which have pubescence and are quite soft. The plants of the sample are well established, quickly regenerate vegetation and are resistant to shedding and falling. The sample is quite drought-resistant, resistant to diseases, especially brown rust. The sample is quite durable and does not lose its decorativeness for 4 years. Sample D07 has a good decorativeness score, a nice light green color of the leaf blade, soft leaves, pubescent. Plants of this form are resistant to seed shedding, grass loss, grow slowly after mowing and do not form clumps. Sample K35591 has good winter resistance and durability, a high score of decorativeness. Forms a good sod cover, rich green color of the leaves. Plants are resistant to diseases, quickly regenerate vegetation and are quite drought-resistant.